2016
DOI: 10.1080/15592324.2016.1249083
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Arabidopsis flooding responses identifies numerous putative “tolerance genes”

Abstract: Plant survival in flooded environments requires a combinatory response to multiple stress conditions such as limited light availability, reduced gas exchange and nutrient uptake. The ability to fine-tune the molecular response at the transcriptional and/or post-transcriptional level that can eventually lead to metabolic and anatomical adjustments are the underlying requirements to confer tolerance. Previously, we compared the transcriptomic adjustment of submergence tolerant, intolerant accessions and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Many traits related to abiotic stress such as salt, drought, heat, and freezing tolerance have been analyzed by GWAS in Arabidopsis ( Baxter et al, 2010 ; Li et al, 2010 ; Verslues et al, 2014 ; Horton et al, 2016 ). A GWAS using 81 Arabidopsis accessions identified 30 significant SNP markers ( p < 10 −4 ) associated with a survival score after submergence ( Vashisht et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many traits related to abiotic stress such as salt, drought, heat, and freezing tolerance have been analyzed by GWAS in Arabidopsis ( Baxter et al, 2010 ; Li et al, 2010 ; Verslues et al, 2014 ; Horton et al, 2016 ). A GWAS using 81 Arabidopsis accessions identified 30 significant SNP markers ( p < 10 −4 ) associated with a survival score after submergence ( Vashisht et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cause of these changes is the dramatic reprogramming of gene expression and RNA molecules, including coding RNA (mRNA) and non-coding RNA (ncRNA) that has been quantified with the development of deep high-throughput sequencing [4,5]. Numerous investigations into Arabidopsis [6][7][8], rice [9], maize [10,11], poplar (Populus × canescens) [12], and cotton (Gossypium hirsutum) [13] have been conducted to elucidate changes in the gene transcription of mRNA in response to low oxygen or flooding stress; these studies have revealed the similarity in transcriptome responses among species [14,15]. However, knowledge of ncRNA involved in hypoxia responses is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Through genome-wide association analysis combined with biparental QTL mapping approaches, candidate gene HXK6 encoding a hexokinase was identified, with its role in mediating seed germination and contributing to the differences in coleoptile growth between Japonica and Indica varieties under submerged condition (Hsu and Tung, 2015). In Arabidopsis thaliana , genome wide association analysis on 81 natural accessions detected 77 genes (within 10 kb of the associated SNP markers) significantly associated with submergence response and involved in many physiological processes including carbon starvation and fermentation (Vashisht et al, 2016). These genes are important regulators for controlling diverse plant responses to submerged conditions.…”
Section: Introductionmentioning
confidence: 99%